1990
DOI: 10.1068/p190017
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Causality Occurs with Stroboscopic Movement of One or Both Stimulus Elements

Abstract: It was shown by magnitude estimation that the perception of causality first described by Michotte (1946/1963) also occurs consistently and strongly with stroboscopic, ie apparent or phi, movement. This is so when the 'causal' movement is stroboscopic and the 'caused' movement real, when these movements are reversed, and when both movements are stroboscopic. The effect is not due to prior experience with Michotte-type displays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…Observers of this stimulus reliably report a perceptual impression that A makes B move; in other words, they perceive B's motion as caused by A bumping into it. This perceptual impression was first reported by Michotte (1946), who called it "l'effet lancement," translated into English as the launching effect (Michotte, 1963), and many subsequent studies have confirmed it as a reliable feature of perception (Gordon, Day, & Stecher, 1990;Scholl & Tremoulet, 2000).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Observers of this stimulus reliably report a perceptual impression that A makes B move; in other words, they perceive B's motion as caused by A bumping into it. This perceptual impression was first reported by Michotte (1946), who called it "l'effet lancement," translated into English as the launching effect (Michotte, 1963), and many subsequent studies have confirmed it as a reliable feature of perception (Gordon, Day, & Stecher, 1990;Scholl & Tremoulet, 2000).…”
mentioning
confidence: 89%
“…People do not see B as making A stop. Support for this claim consists of an absence of evidence for any report that observers see B making A stop (Gordon et al, 1990;Michotte, 1963;Schlottmann, Ray, Demetriou, & Mitchell, 2006;White, 2006). There does not appear to have been any study in which participants were asked to report their impressions of the forces exerted by the objects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At that point, Object A stops moving and Object B starts moving, typically with the same speed as Object A or slightly less. This stimulus reliably evokes a causal impression: Observers consistently report an impression that Object A brings about or produces Object B's motion by striking it, an impression known as the launching effect (Gordon, Day, & Stecher, 1990;Michotte, 1963;Natsoulas, 1961;Schlottmann, Ray, Mitchell, & Demetriou, 2006;Scholl & Tremoulet, 2000).…”
mentioning
confidence: 97%
“…This project also began with Michotte (1946Michotte ( /1963, who-in the course of over 100 experiments in the English translation of his landmark bookworked out the details of how perceptual causality is impacted by the absolute and relative speeds of the objects, the distances and directions in which they travel (both before and after "impact"), various types of spatial and temporal gaps, and many other variables. More recent investigations have continued this project, exploring how the perception of causality is affected by different types of motion (e.g., apparent motion; Gordon, Day, & Stecher, 1990), the use of more than two interacting objects (e.g., the tool effect; Michotte & Thinès, 1963/1991, other types of spatiotemporal gaps (e.g., Schlottmann & Anderson, 1993), other modalities (e.g., Guski & Troje, 2003), and many other factors (e.g., Boyle, 1960;Gemelli & Cappellini, 1958;Hubbard, Blessum, & Ruppel, 2001;Kruschke & Fragassi, 1996;Natsoulas, 1961;Schlottmann, Allen, Linderoth, & Hesket, 2002;Schlottmann & Shanks, 1992;Weir, 1978;White, in press;White & Milne, 1997, 1999Yela, 1952).…”
Section: Effects Of Grouping and Attentionmentioning
confidence: 99%